H HUBUNGAN MOTIVASI TERHADAP KEPATUHAN PENGOBATAN PADA PENDERITA DIABETES MELITUS TIPE II - Prasetya, Septa Adhi; Irawan, Angga; Rahman, Subhannur (LPPM Universitas Sari Mulia, 2023)
Background: In the era of globalization there has been a shift from communicable diseases to non-communicable diseases, degenerative diseases are increasingly appearing, one of which is diabetes mellitus. One of the efforts to prevent and treat diabetes mellitus patients is to provide motivation in medication adherence in diabetes mellitus patients. Good motivation will affect increased compliance. Compliance in adhering to treatment plays an important role in maintaining the balance of blood sugar levels and minimizing the risk of complications. Objective: To find out the correlation between motivation and adherence to treatment in patients with diabetes mellitus type II at the PIR Butong Health Center. Methods: This type of quantitative research with a correlational study design with a cross sectional approach. The sample was type II diabetes mellitus patients who underwent routine treatment at the PIR Butong Health Center in January - February 2023 totaling 63 people and were taken using the accidental sampling technique. Retrieval of data using a questionnaire sheet. Data analysis used the Spearman Rho test. Result: Most of the respondents had good motivation, namely 33 people (52.4%), almost half of the respondents had low medication adherence, namely 23 people (36.5%). There is a significant relationship between motivation and medication adherence in type II. diabetes mellitus at the PIR Butong Health Center with a p-value (0.000<0.05). The value of r = -0.615 which means a high correlation coefficient or a high relationship between motivation and medication adherence. Conclusion: There was a correlation between motivation and adherence to treatment in patients with diabetes mellitus type II at the PIR Butong Health Center.